Conquer and govern: early Chinese military texts from the Yi Zhou shu by Robin McNeal [Book review] - Graff, David A. (My University, 2014)
Review of Conquer and Govern: Early Chinese Military Texts from the Yi Zhou shu. By Robin McNeal. (Honolulu: University of Hawai’i Press, 2012. Pp. viii, 246. $48.00.)
Keywords: Chinese military texts; Book review; Yi Zhou shu; McNeal, Robin